Study of Durability of Concrete with Fly Ash as Fine Aggregate under Alternative Interactions of Freeze-Thaw and Carbonation - Mingjie Mao; Dongsheng Zhang; Qiuning Yang; Wenbo Zhang (Advances in Civil Engineering)
To study the durability of concrete with fly ash as fine aggregate subjected to alternative attacks of freeze-thaw and carbonation, the appearance, mass loss, relative dynamic modulus of elasticity, relative compressive strength, and carbonation depth of the concrete are investigated using cyclic tests under single carbonation, single freeze-thaw, and alternation of freeze-thaw and carbonation. In addition, microstructural analysis techniques including scanning electron microscope and X-ray diffraction are adopted to reveal the deterioration mechanism of alternating freeze-thaw and carbonation. Results show that carbonation is beneficial for refining the pore structure and increasing concrete strength in the initial alternative cycle, which delays the damage from freeze-thaw cycles. Damage from freeze-thaw causes crack propagation in concrete, which leads to carbonation intensification. Compared with other test modes, concrete under alternative freeze-thaw and carbonation causes the greatest degree of deterioration during the initial freeze-thaw cycles. The carbonation depth under alternative freeze-thaw and carbonation is positively correlated with the carbonation time and the water-to-cement ratio. However, as the reactant is continuously consumed due to the expansion of crystalline ice and CaCO3, alternative cycles result in the appearance of many more new cracks in the concrete.